1966
DOI: 10.1243/pime_conf_1966_181_295_02
|View full text |Cite
|
Sign up to set email alerts
|

Paper 19: Unlubricated Sliding at High Speeds between Copper and Steel Surfaces

Abstract: Experiments are described in which stationary copper specimens are rubbed in a normal atmosphere against a rotating S62 steel disc under normal loads up to 4·5 lbf. The coefficient of friction is measured at sliding speeds of 93, 220, 328, and 490 ft/s using ⅛-in diameter specimens. Except at the lowest speed a gradual buildup of a continuous copper oxide layer on the disc track is observed with increasing normal load together with a corresponding decrease in the coefficient of friction. Having established an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Experiments (using, for example, a high speed pin-on-disk test device) have shown that at large sliding velocities a reduction of the friction coefficient is obtained when the normal pressure or the sliding velocity is increased (Williams and Griffen, 1964;Kadhim andPowell, 1966-1967;Montgomery, 1976;Lim et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments (using, for example, a high speed pin-on-disk test device) have shown that at large sliding velocities a reduction of the friction coefficient is obtained when the normal pressure or the sliding velocity is increased (Williams and Griffen, 1964;Kadhim andPowell, 1966-1967;Montgomery, 1976;Lim et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…By post examination of the tips of the projectile he studied the evolution of the melt process during the penetration event. Williams and Gri en (1964), Montgomery (1976b), Kadhim and, Powell (1966-1967) and Lim et al (1989) conducted high speed sliding experiments using a high-speed pin-on-disk test device. The results of these studies indicate a reduction in the coe cient of friction when the normal pressure and/or the sliding velocity were increased.…”
Section: Introductionmentioning
confidence: 99%